A Framework to Determine the Maintenance Performance in the Water and Sewerage Companies; The Case Study: Alborz Water and Sewerage Company - Reza Shahrjerdi (علوم و مهندسی آب و فاضلاب, 2023)
Nowadays, due to the large volume of assets in the water and wastewater industry and its impact on the development and sustainability of other industries, specific attention to this industry becomes more apparent. Since there are various equipments in this industry, achieving efficiency and proper performance in this equipment and maintenance system has been identified and then, with fuzzy decision-making which can be envisaged as innovation of this project, the ranking of the factors has been worked upon. The results of this requires timely maintenance and repairs. This study has evaluated the efficiency of these systems by considering the importance of paying attention to the factors that affect the performance of the maintenance system and consequently the quality and reliability. Considering the various evaluation and ranking methods, the present research has investigated this issue in two phases using operations research techniques and fuzzy decision making. In the first, the pivotal factors on the Alborz Province Water and Sewage Company’s function of upkeep study shows that water and sewage companies by employing of technological conditions that include quality and utilization of innovative technologies that have highest priority in comparison to other important alternatives with ultimate importance of 0.3123 could increase productivity.